AUDITORÍA A LOS ESTADOS FINANCIEROS DE “SU COMISARIATO” DE LA CIUDAD DE CATAMAYO, PERÍODO 2013 - Herrera Camacho, Maribel del Cisne (2015)
The theme of this work is entitled STATES FINANCIAL AUDIT A "SU commissary" CITY OF PERIOD CATAMAYO 2013, it was developed to meet a prerequisite to choose the Engineering degree in Accounting and Auditing at the National University of Loja, on the other hand its purpose was to provide a contribution to the decision to company owner. Had as main objectives the implementation of an Audit of the Financial Statements for the year 2013 on "YOUR commissary" Catamayense city for which it was necessary, evaluate the internal control system in the company to control its economic activities and financial, determine the reasonableness with which the accounts of the financial statements presented. And verify the compliance of laws by the owner and employees of the company. Analyze and evaluate the procedures performed in the management of the financial activities of the main accounts that comprise the financial statements of the company. Issue a report containing comments, conclusions and recommendations, all this in order to improve the functioning of the company. In the first part we developed a bibliographic research by consulting manuals books, magazines and other publications that relate to the topic, this in order to structure a conceptual and theoretical framework, which 6 helped to understand the problem at best, there consist concepts and definitions of the audit in the private sector. A second part of the work consists Financial Audit practice of States, it was developed by observing the Generally Accepted Auditing Standards, Internal Control Standard applicable to the private sector after relevant laws governing Institutional life. Based on the work order, continue with Phases which are developed in this kind of work, and Phase. Planning after the previous visit in which information was compiled are presented the Preliminary Planning, and Planning Specifies, in the latter strategy appears to follow in the field after evaluating the internal control system, the results reflected in the narratives cedulas, continues with Phase Two: fieldwork, audit programs here are developed through a series of procedures that made possible the preparation of working papers where the most important findings consist then gather sufficient competent evidence to substantiate her serve Final Report. It continues with the third phase; The communication of results, which is the work of the Financial Audit, constituted Discussion in the report, which contains opinions, conclusions and recommendations that will allow the business owner timely and appropriate decisions to improve their management. After the investigation, the conclusions and recommendations of the research are presented and consulted bibliography plus appendices thereo.